2012
DOI: 10.1021/ja302897b
|View full text |Cite
|
Sign up to set email alerts
|

α-Sulfur Crystals as a Visible-Light-Active Photocatalyst

Abstract: We show that in contrast to conventional compound photocatalysts, α-sulfur crystals of cyclooctasulfur (S(8)) are a visible-light-active elemental photocatalyst. The α-S crystals were found to have the ability not only to generate ·OH radicals but also to split water in a photoelectrochemical process under both UV-vis and visible-light irradiation. Although the absolute activity obtained was low because of the large particle size and poor hydrophilicity of the α-S crystals studied, there is great potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(304 citation statements)
references
References 23 publications
9
293
0
2
Order By: Relevance
“…The highly intense peak at 2θ of 52.7 for a d=7.14 as observed in XRD pattern of raw sulphur were found to diminish to an intensity of 200 Lin counts in processed sulphur samples [15] , and it was also observed that sulphur existed in the processed sample both in its elemental and compound forms. The change in intensity of peak in XRD pattern for processed sulphur was associated with physical rearrangement of atoms such as additional bonding to other atoms.…”
Section: Fig 3: Xrd Spectrum Of Sulphur Before Process (A) After Promentioning
confidence: 80%
“…The highly intense peak at 2θ of 52.7 for a d=7.14 as observed in XRD pattern of raw sulphur were found to diminish to an intensity of 200 Lin counts in processed sulphur samples [15] , and it was also observed that sulphur existed in the processed sample both in its elemental and compound forms. The change in intensity of peak in XRD pattern for processed sulphur was associated with physical rearrangement of atoms such as additional bonding to other atoms.…”
Section: Fig 3: Xrd Spectrum Of Sulphur Before Process (A) After Promentioning
confidence: 80%
“…The most efficient metal-free photocatalyst is the graphitic carbon nitride (g-C 3 N 4 ). [74][75][76][77][78] For instance, Wang et al [79] reported that the carbon nitride (C 3 N 4 ) polymer can be easily modified by standard organic protocols. The copolymerization with barbituric acid was studied and realized the continuous band structure modification.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…This may be attributed to the surface plasmon absorption effect of Ag NPs deposited on the surface of composites [38] , which would strengthen their antibiotic capability. Fluorescence method with terephthalic acid (TA) as the probe was employed for the quantification of •OH radicals [39,40] . The unique fluorescence signal peaked at 426 nm were observed (Fig.…”
Section: Synergistic Antibacterial Mechanism Of Tio 2 /Ag Compositesmentioning
confidence: 99%